2015
DOI: 10.5505/tjtes.2015.91298
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relationship between Violence and Burnout among Physicians Working in Emergency Departments, Turkey

Abstract: BACKGROUND: Violence and burnout are frequently seen among medical doctors; however, the relation is not clear. This study aimed to assess the violence and its possible effects on burnout in physicians working in emergency units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…The model was used to explore the relationships between emotional labour, workplace violence and burnout and particularly suggests that emotional labour influences burnout through its effect on workplace violence. In previous studies related to burnout, greater emotional labour (Cheng et al, 2013;Edward et al, 2017) and workplace violence experience (Chen et al, 2016;Choi & Lee, 2017;Erdur et al, 2015;Waschgler et al, 2012;Yoon & Sok, 2016;Zafar et al, 2015) were found to be associated with higher burnout. Although the focus was not on nurses, previous research has found that there was an association between the study of hotel workers and the relationship between language violence and emotional labour (Jung, Kim, & Lee, 2015).…”
Section: Hypothetical Modelmentioning
confidence: 77%
See 1 more Smart Citation
“…The model was used to explore the relationships between emotional labour, workplace violence and burnout and particularly suggests that emotional labour influences burnout through its effect on workplace violence. In previous studies related to burnout, greater emotional labour (Cheng et al, 2013;Edward et al, 2017) and workplace violence experience (Chen et al, 2016;Choi & Lee, 2017;Erdur et al, 2015;Waschgler et al, 2012;Yoon & Sok, 2016;Zafar et al, 2015) were found to be associated with higher burnout. Although the focus was not on nurses, previous research has found that there was an association between the study of hotel workers and the relationship between language violence and emotional labour (Jung, Kim, & Lee, 2015).…”
Section: Hypothetical Modelmentioning
confidence: 77%
“…Other studies on nurses' burnout have reported that exposure to workplace violence is another factor influencing burnout (Chen, Lin, Ruan, Li, & Wu, 2016;Choi & Lee, 2017;Erdur et al, 2015; Waschgler, Ruiz-Hern andez, Llor-Esteban, & Garc ıa-Izquierdo, 2012; Yoon & Sok, 2016;Zafar, Khan, Siddiqui, Jamali, & Razzak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by results from a Turkish study that showed a statistically signi cant relationship between burnout and violence experienced by EPs working in the EDs. 56 Our current study had a relatively good sample size and response rate, and it is among the few attempts to use the CBI to measure burnout in EPs, and to add the SOS-S as an additional stress measuring tool for construct validity purposes. We aimed to compare our data with the local GCC countries and international literature.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, burnout has been reported as a frequent problem seen in emergency service physicians 22 . A direct correlation has been demonstrated between burnout and exposure to assault in emergency service physicians 21 . In general, burnout has been found to be strongly associated with anxiety disorders 23 .…”
Section: Medical Specialtymentioning
confidence: 95%
“…Emergency service physicians are exposed to numerous occupational dangers, which include infectious diseases, latex allergy, exposure to nitrous oxide, working in shifts, exposure to violence, and emotional stress 20 . Exposure to verbal or physical assault is quite common in emergency service workers 21 . In addition, burnout has been reported as a frequent problem seen in emergency service physicians 22 .…”
Section: Medical Specialtymentioning
confidence: 99%